Helicopters an illustrated history of their impact - McGowen, Stanley S (Weapons and warfare series., 2005)
Helicopters: An Illustrated History of Their Impact covers the development of helicopters from a concept in Leonardo daVinci's mind to the first successful machines in the early 1900s to the latest tilt-rotor designs. Time and again, in a story of constant innovation, designers answered the concerns of military planners with more maneuverable, more capable rotorcraft. With expert analysis and specific details of every significant model ever used, Helicopters shows how these once denigrated machines became essential to a variety of missions (reconnaissance, transport, attack, support, evacuation, urban combat, quick strikes behind enemy lines, and more). In addition, the book looks at the impact of rotorcraft beyond the military, including their ever-widening role in emergency medical care, police work, traffic control, agriculture, news reporting, and more.